Use of Interpersonal Counseling for Modern Type Depression - Ono, Hisae; Yamamoto, Ami; Taketani, Reiko; Tsujimoto, Emi (Case Reports in Psychiatry, 2017)
A novel form of depression, called “modern type depression” (MTD), has been increasing in prevalence in Japan. Patients with MTD present with an overt appeal of depressive mood and a desire to be excused from their work duties; as such, this can cause considerable trouble in the workplace. Psychosocial interventions should be primarily considered for the treatment of MTD. Interpersonal counseling (IPC), which has proven effective for treating subthreshold depression, may be effective for MTD. However, IPC is rarely done in Japan. Herein, we report on a successful case of IPC for a woman in her thirties who was about to quit her job due to MTD (diagnosed by the criteria for research use). After IPC, the patient enjoyed good communication with her boss and continued her job without succumbing to her depression. This case suggests that IPC may be effective for MTD in workers and further highlights the benefits of teaching interpersonal communication methods in the workplace.